2015
DOI: 10.1159/000430322
|View full text |Cite
|
Sign up to set email alerts
|

Calhex231 Ameliorates Cardiac Hypertrophy by Inhibiting Cellular Autophagy in Vivo and in Vitro

Abstract: Background/Aims: Intracellular calcium concentration ([Ca2+]i) homeostasis, an initial factor of cardiac hypertrophy, is regulated by the calcium-sensing receptor (CaSR) and is associated with the formation of autolysosomes. The aim of this study was to investigate the role of Calhex231, a CaSR inhibitor, on the hypertrophic response via autophagy modulation. Methods: Cardiac hypertrophy was induced by transverse aortic constriction (TAC) in 40 male Wistar rats, while 10 rats u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…Nakai et al reported that cardiomyocytes manifest a classical hypertrophic response with a reduced autophagic activity [11], while Kanamori et al reported that during nutrient deprivation, suppressed autophagy leads to reduced cardiac ATP content and impaired heart performance [12]. Furthermore, studies with human samples and pressure overload animal models have suggested that excessive autophagy activity may play a maladaptive role in heart failure pathogenesis [13-17]. In the present study, we found excessive autophagy activity in the myocardium of animals subjected to the TAC operation, correlated with myocardium hypertrophy and cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Nakai et al reported that cardiomyocytes manifest a classical hypertrophic response with a reduced autophagic activity [11], while Kanamori et al reported that during nutrient deprivation, suppressed autophagy leads to reduced cardiac ATP content and impaired heart performance [12]. Furthermore, studies with human samples and pressure overload animal models have suggested that excessive autophagy activity may play a maladaptive role in heart failure pathogenesis [13-17]. In the present study, we found excessive autophagy activity in the myocardium of animals subjected to the TAC operation, correlated with myocardium hypertrophy and cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The observed cardiac remodeling, i.e., stronger mode of contraction, together with the increase in dp/dt, could thus be interpreted as compensatory response to the bradycardic and hypotensive phenotype. The reduction in fibrosis suggests that KO animals might be protected against the development of age-related cardiac fibrosis (2), maybe via a beneficial effect of their reduced heart rate (8) but could also be a direct consequence of CaSR deletion from the heart, as recently indicated in a rat model of cardiac hypertrophy (32). Further studies will be necessary to completely elucidate the role of the cardiac CaSR.…”
Section: Vascular Phenotypementioning
confidence: 99%
“…Many signaling pathways have also been found to be involved in Ang II-induced autophagy, for example, Calhex231 suppressed calcium-sensing receptor (CaSR) expression and downregulated autophagy by inhibiting the Ca 2+ /calmodulin-dependent protein kinase-kinase-β (CaMKKβ)-AMPK-mTOR pathway to ameliorate cardiomyocyte hypertrophy induced by Ang II in neonatal rat cardiomyocytes (Liu et al 2015). Ang II exposure induced significant increase in the expression of endogenous intermedin in H9c2 cell cultures and mouse hearts, and the sizes of cardiomyocyte, interstitial collagen, ANP and BNP expression were also increased.…”
Section: Other Signaling Pathways In Ang Ii-induced Autophagymentioning
confidence: 99%